Fixed Mindset And Pronunciation Skills: A Study Of 5th Semester English Students - Laoli, Jacqueline; Okta Christoper Laoli; Sharley Grace Mendrofa; Adieli Laoli (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2025)
This study examines how a fixed mindset affects university students' English pronunciation, focusing on students in Nias University's English education program. A fixed mindset, the belief that abilities are unchangeable, impacts students' motivation to learn pronunciation. Using purposive sampling, ten participants were selected, and semi-structured interviews explored their mindset-related challenges. Thematic analysis revealed that students with a fixed mindset struggled to improve pronunciation due to fear of failure, avoidance of challenges, and reluctance to accept feedback. In contrast, those with a growth mindset showed persistence, openness to criticism, and willingness to learn from mistakes. The study highlights the crucial role of mindset in language learning, especially in overcoming pronunciation difficulties. Findings suggest the need to foster a growth mindset among learners. Teachers should create engaging learning environments, provide constructive feedback, and encourage perseverance. This research contributes to understanding how mindset influences language acquisition, particularly English pronunciation.